Aplikasi Location Based Service (LBS) Objek Wisata Tanggamus Berbasis Android - M Budi Hartanto; Yodhi Yuniarthe (Universitas Mitra Indonesia, 2020)
AbstractThe presence of smartphones with various existing applications has an impact on the lives of the surrounding community. Various applications are present and always growing in this tourism sector. One of them is as a digital introduction media for destinations in Tanggamus Regency which contains information needed by tourists, facilities, rides offered and other supporting facilities such as gas stations, ATMs, police stations, workshops and so on. Tanggamus Regency is a district located in Lampung Province which has several natural tourist sites that are worth visiting, but there are still many people who are not very familiar with the existing destinations. This occurs due to the lack of exposure and lack of introduction to the wider community in various regions. In addition, there is no android-based application system that serves to introduce and convey information on tourist destinations to the wider community and there is no special digital media that promotes Tanggamus tourism. One solution to solve the problems that arise is to build a Location Based Service (LBS) application as a geographic information system (GIS) point with an Android-based user interface. The results of the LBS application for tourist destinations in Tanggamus Regency are in the form of an information system that is able to provide details of tourist locations and can introduce tourism locations in Tanggamus Regency more widely so that it makes it easier for the public to know and can become a technology-based marketing or introduction media and tourists who want to take a vacation no longer need to search for information via google with lots of keywords.